EFCAB10 anchors AK8 to the radial spoke for proper ciliary motility - Ting Song; Qingchao Li; Qian Lyu; Junkui Zhao; Xirui Zi; Shuxiang Ma; Jiajun Luo; Shushen Li; Shanshan Nai; Hongbin Liu; Xueliang Zhu; Te Li; et al. (Proceedings of the National Academy of Sciences, 2025)
Radial spokes in motile cilia and flagella regulate rhythmic ciliary motility, which is essential for rapid cell movement and extracellular fluid flow. In humans, defective radial spokes can cause a genetic disorder known as primary ciliary dyskinesia (PCD), resulting in respiratory defects and infertility. Despite their critical role in ciliary motility, the molecular composition and related physiological functions remain to be elucidated. Here, we identify EF-hand calcium-binding domain protein 10 (EFCAB10) and adenylate kinase (AK8) as radial spoke proteins and describe their roles in mouse motile cilia. Using Efcab10 −/− and Ak8 −/− mice, we show that loss of either protein can affect ciliary motility and lead to PCD-related phenotypes in mice. Interestingly, ciliary AK8 is completely absent in Efcab10 −/− cilia, but the loss of AK8 has no effect on ciliary EFCAB10. Further biochemical analyses reveal that EFCAB10 interacts with AK8 and RSPH3B, which fastens AK8 to the radial spoke. Overall, our findings demonstrate the essential role of EFCAB10 as a radial spoke protein in maintaining the integrity of the radial spoke and provide valuable insights into the molecular basis of related ciliopathies.